2014
DOI: 10.3168/jds.2013-7419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prepubertal and postpubertal growth and age at first calving on production and reproduction traits during the first 3 lactations in Holstein dairy cattle

Abstract: The objective of this study was to evaluate the effect of body condition score (BCS), body weight (BW), average daily weight gain (ADG), and age at first calving (AFC) of Holstein heifers on production and reproduction parameters in the 3 subsequent lactations. The data set consisted of 780 Holstein heifers calved at 2 dairy farms in the Czech Republic from 2007 to 2011. Their BW and BCS were measured at monthly intervals during the rearing period (5 to 18 mo of age), and the milk production and reproduction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…The age at first calving, despite being intensively selected in Holsteins, deserves attention in animal breeding programs, once it can influence other reproductive and productive traits. Krpálková et al (2014) demonstrated that cows with earlier calving have fewer days open, reduced service numbers, shorter interval to conception, as well as increased milk production in the second and third lactations.…”
Section: Resultsmentioning
confidence: 99%
“…The age at first calving, despite being intensively selected in Holsteins, deserves attention in animal breeding programs, once it can influence other reproductive and productive traits. Krpálková et al (2014) demonstrated that cows with earlier calving have fewer days open, reduced service numbers, shorter interval to conception, as well as increased milk production in the second and third lactations.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies suggest that the earlier the age at the first calving the better (Shamay et al 2005;Stevenson et al 2008). Krpálková et al (2014b) concluded that the lowest average milk yield in the lifetime production was observed in the age at the first calving higher than 24.5 months of age.…”
Section: High-producing Dairy Herdmentioning
confidence: 99%
“…Ettema and Santos (2004) showed that in the USA from the economic point of view the most advantageous age at first calving in primiparous Holstein cows is 23-24.5 months. In another study Krpálkova et al (2014a) found no negative effect of a young age at first calving (≤ 699 days) on milk production and reproduction. However, in a different study Krpálkova et al (2014b) suggested that a younger age at first calving (≤ 749 days) is not always profitable, as it is determined by the herd management standard.…”
Section: Discussionmentioning
confidence: 88%